2017
DOI: 10.1017/s1431927617008881
|View full text |Cite
|
Sign up to set email alerts
|

Solid State Transition from γ to α-Al2O3 Induced by SPEX Mechanical Milling

Abstract: The high energy ball milling is an easy and low cost technique that has been highly used in the processing of powder materials. This technique has demonstrated to be effective in the synthesis of new compounds, formation of solid solutions, production of nanostructured materials, activation of powders and homogenization of phases [1]. In this study we report the use of the SPEX mechanical milling to synthesize α-Al 2 O 3 from γ-Al 2 O 3 . The γ-Al 2 O 3 was obtained by the calcination of pseudoboehmite at 500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(4 reference statements)
1
1
0
Order By: Relevance
“…This happened because the precursors coming from pure reagents did not contain small seeds of transition phases. The dates collected in this study for α-Al2O3, were obtained at ambient temperature and confirmed by other authors [122,124,125].…”
Section: Mechanical Activation Of Boehmite -Transition γ Al2o3 To α-A...supporting
confidence: 88%
See 1 more Smart Citation
“…This happened because the precursors coming from pure reagents did not contain small seeds of transition phases. The dates collected in this study for α-Al2O3, were obtained at ambient temperature and confirmed by other authors [122,124,125].…”
Section: Mechanical Activation Of Boehmite -Transition γ Al2o3 To α-A...supporting
confidence: 88%
“…Cortés-Vega et al found a reasonable solution to produce α-Al2O3 of good quality using as the initial precursor, the pseudo-boehmite synthesized by the reaction in an aqueous environment of aluminum sulfate or nitrate with gaseous ammonia [124]. The washed and dried pseudo-boehmite powder is thermally transformed, at a temperature of 300-500ºC, into γ-Al 2 O 3 .…”
Section: Mechanical Activation Of Boehmite -Transition γ Al2o3 To α-A...mentioning
confidence: 99%